Mortality attributable to tobacco: review of different methods - Tachfouti, Nabil (BioMed Central, 2014)
BACKGROUND: One of the most important measures for ascertaining the impact of tobacco is the estimation of the mortality attributable to its use. Several indirect methods of quantification are available. The objective of the article is to assess methodologies published and applied in calculating mortality attributable to smoking. METHODS: A review of the literature was made for the period 1998 to 2005, in the electronic databases MEDLINE. Twelve articles were selected for analysis. RESULTS: The most widely used methods were the prevalence methods, followed by smoking impact ration method. Ezzati and Lopez showed that the general rate of Smoking attributable mortality (SAM) globally was 12% (18% in men). Across countries, attributable fractions of total adult deaths ranged from 8% in Southern Africa, 13.6% in Brazil (18.1% in men) and 25% in Hong Kong (33% in men). CONCLUSION: The variations can be attributed to methodological differences and to different estimates of the main tobacco-related illnesses and tobacco prevalence. All methods show limitations of one type or another, yet there is no consensus as to which furnishes the best information.